Formation of national identity in Central Asia - Uskembayeva, А.А. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article the phenomenon of national identity as a multidimensional process of the formation of a person and a nation, which can be revealed through various aspects is discussed. The author's position on the problem of modern interpretation of the concepts of «identity» and «national identity» is presented. The paper reveals the specifics of the formation of national identity in the countries of Central Asia. Central Asia, one of the most understudied areas in the world, is currently going through the upheavals of modernisation and nation formation. Arguing against the one-dimensional modernist conclusion that this process was arrested during the Soviet period, the article sets out to explore the complex weave of historical continuity and discontinuity in the formation of national identity in the new states. It argues against the notion that national identity involves the necessary dissolution of traditional ties. Based on the above, the author comes to the conclusion that national identity can be defined as a complex multidimensional, multifaceted phenomenon, the study of which includes social, socio-philosophical, psychological, culturological, properly ethnic aspects. Identity bears in itself the answer to the question about the essence of its people, nation, its place, role and tasks in world history and the ideal forms of its existence. Thus, national identity develops in the process of historical change, characterizing a certain level of growth of national self-consciousness.
Орталық Азиядағы ұлттық бірегейліліктің қалыптасуы
Формирование национальной идентичности в Центральной Азии
Keywords: identity; national identity; culture; history; nation; Central Asia; Union; language; heritage; formation